FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA AKUNTANSI FE UST MENGIKUTI UJIAN SERTIFIKASI AKUNTAN PUBLIK (USAP) - Adia Adi Prabowo (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
Students who want to work as public accountants are required to first take thePublic Accountants Certification Exam which is held by the Indonesian Instituteof Certified Public Accountants, but students who take the public accountantcertification exam are still minimal. The purpose of this study is to determine theeffect of economic motivation, personality, barriers, social motivation and qualitymotivation on accounting students’ interest in taking the Public AccountantCertification Exam.The research respondents were all students of semester VIand above Accounting Study Program Department of AccountingSarjanawiyataTamansiswa University. The instrument testing was carried out usingvalidity and reliability tests. To determine the accuracy of the model, classicalassumption testing is carried out followed by multiple regression analysis bothpartially and simultaneously. The results of this study indicate that the variablesof economic motivation, personality, exam barriers, social motivation and qualitymotivation simultaneously influence the interest of accounting students takingthe Public Accountant Certification Exam by explaining the variation expressedin the coefficient of determination, showing that 66.6% of the variation in interestdetermined by social motivation and personality, while 33.4% is determined byother variables not examined in this study but partially personality and socialmotivation have a significant influence on the interests of accounting studentstaking the Public Accountant Certification Exam, while economic motivationvariables, test barriers, and quality motivation does not have a significant influenceon the interests of accounting students taking the Public Accountant CertificationExam.